PERKEMBANGAN DAN PENINGGALAN DINASTI MOGHUL DI INDIA 1525-1857 - Supardi Supardi (Universitas Negeri Yogyakarta, 2008)
Abstract There are three objectives to writing this article as follow, First is to know the background of the rise of Moghul Empire, Second to know growth and fall of the Moghul Empire, and the last several Moghul legacies such as in the aspect of politic, social, art, etc.The founding father of Moghul Empire is Kutbu’ddin Aibak (1206-1211), who was able to establish Independence Islamic Kingdom of India. There are several ruler: Sultan Akbar, Syah Jahan, dan Aurangzib. Sultan Akbar has reputation as the ruler who was able to maintain stability of the empire as well as to combine the Islamic and Hindus civilization. Meanwhile Syah Jahan inherit some relics, such as the famous Taj Mahal.Other ruler Aurangzib was to expand his empire. But the generation after Aurangzib fail to maintain unity of his empire and Moghul breakdown to several independence kingdom. The Sepoy Mutiny in 1857 is the end of Moghul Empire. British replace Moghul Empire and occupied whole India until 1947.Keywords: Moghul Empire, Moghul inheritance, India.